143k views
5 votes
Noah wanted to check his solution of x= 14/15 for the equation (7x - 6) = 6x – 10.

Substituting 14/5 for x
1/2 (7( 14/5) -6) = 6 (14/5) -10
(7( 14-/5) -6) = 12 (14/5) -20
5( 7( 14/5) -6) = 5 (12( 14/5) -20)
7•14-6=12•14-20
98-6=168-20
92=148
Find the correct step in Noah’s work and explain why it is incorrect?

2 Answers

6 votes

Answer:

answer????

Explanation:

User MartinWebb
by
5.4k points
1 vote

Answer:

Between step 3 and step 4

Explanation:

User Timkl
by
5.8k points